1990
DOI: 10.1111/j.1834-7819.1990.tb05883.x
|View full text |Cite
|
Sign up to set email alerts
|

Aptitude testing and the selection of dental students

Abstract: This paper discusses the problems involved in the selection of dental students and the need for some form of aptitude testing. It describes the situation in the United Kingdom both in the past and the present, and then describes in detail the situation in North America (both in the United States and Canada). The Dental Admission Test, its history and the research into its development are described with particular emphasis on the dexterity, perceptual and aptitude components of the test. More recent research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…2,3,5,9,22 Rather than attempting to design another predictive test, the primary aim of this study was to establish whether dentists and dental students have problems with the interpretation of depth and distance. It is obvious that many did have significant problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,9,22 Rather than attempting to design another predictive test, the primary aim of this study was to establish whether dentists and dental students have problems with the interpretation of depth and distance. It is obvious that many did have significant problems.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8,10,11 Although it is acknowledged that manual dexterity is an essential and highly desirable quality for a dental student to possess, and studies have examined vision in dental populations, the number of studies that have examined interactions between manual dexterity and vision are few. 5,9,10 Good eyesight is essential to providing the best dental care for patients. 7,11 It is interesting that dentists and dental students as a group have been found to be recalcitrant regarding frequency of eye examinations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated in reducing student dropout rates, however, its value in assessing manual skills is questionable. 22 Studies showed no clear relationship between secondary school grades and clinical competence in medicine or dentistry. 17 It was suggested that effectiveness and success in medical or dental studies requires not only sound academic ability but also a variety of noncognitive skills and qualities, along with a positive attitude toward the profession.…”
Section: Correlation Between Handwriting Drawing Skills and Dental Smentioning
confidence: 99%
“…Really, dental students should acquire an 'aca demic biomedical knowledge and gain the professional skills and attitudes of a broadly based general practitioner'. 2,[8][9][10][11][12][13][14][15][16][17] Although an admission test (based on a multiple choice test, including ques tions on biology, mathematics, phys ics, chemistry and general culture, on a psycho-attitudinal test and on the high school degree) is in use at the Catholic University of Rome for applicants for the CLOPD, during the past few years we were permitted to systematically investigate BMD, for research purposes, thanks to a specific examination of manual ability, even if it was not intended to have any effect on admission itself. The examin ers' curiosity had been aroused by the fact that even university students who were distinguished both for their school performance and their achievements were rather clumsy at the beginning of practical training, both clinical and in the laboratory.…”
Section: Introductionmentioning
confidence: 99%